Technological-Environmental Evaluation of Potential Hydrogen Production in Chile from Domestic Sewage Sludge - Serafini, D; Garrido-Lazo, R (Elsevier Ltd, 2026)
Steam sludge gasification was analyzed as a technology for hydrogen production from Chilean domestic wastewater. This study examines the thermochemical gasification of sewage sludge using Aspen Plus 12.1 software to develop a comprehensive steady-state equilibrium simulation model. A sensitivity analysis of the operating variables (temperature and pressure) of the process was performed to improve the yields towards hydrogen production. A process was established that involves a drying stage to reduce biomass moisture, a pyrolysis stage for material decomposition, an intermediate nitrogen removal stage (to prevent the formation of unwanted compounds), followed by two gasification stages, and finally, syngas purification. A maximum yield of 42 % was obtained for H2 formation under optimal conditions. The environmental performance and costs of hydrogen production from domestic sewage sludge gasification were evaluated using an LCA and a Levelized Cost of Hydrogen approach. In addition, the unit costs of carbon reduction associated with replacing conventional technologies with the one proposed in this study were assessed. The environmental profile of hydrogen from biomass gasification was compared with that calculated for hydrogen from conventional steam methane reforming, based on inventory data also obtained through process simulation. In the proposed process, lower environmental impact values were obtained, especially in categories such as global warming, fine particulate matter formation, and terrestrial acidification (with reductions of 88 %, 64 %, and 87 %, respectively). Overall, biohydrogen obtained by gasification proved to be a promising and commercially competitive fuel, with production costs of $4.02 USD/kg-H2, and lower carbon abatement costs compared to conventional technologies. © 2025 Elsevier Ltd